Polymorphism analysis of kisspeptin (KISS1) gene and its association with litter size in Ethiopian indigenous goat populations - Mekuriaw, Getinet; Mwacharo, Joram M.; Dessie, Tadelle; Okeyo Mwai, Ally; Djikeng, Appolinaire; Osama, S.; Gebreyesus, G.; Kidane, A.; Abegaz, Solomon; Tesfaye, K. (Academic Journals, 2017)
Polymorphism analysis of the Kisspeptin (KISS1) gene and its association with litter size were conducted in two (Gondar and Woyto Guji) Ethiopian indigenous goat populations. Three new pairs of primers were designed for touchdown PCR condition. A total of 173 and 242 Sanger sequences were employed for further analysis of exon1 (1210 bp) and exon2 (325 bp) regions of the KISS1 gene, respectively. In addition, the identified polymorphic sites were associated with litter size of the animals included in the study. General linear model was carried out for the association analysis. The study revealed that five complete substitutions and 15 polymorphic sites were detected in both exon regions with 2:1 transition and transversion ratio. Most of the polymorphic sites were observed in more than 1% of the sequences qualifying the single nucleotide polymorphisms (SNPs) definition. The overall average codon bias index was 0.301 with 64.09 and 62.47% GC contents in exon1 and exon2, respectively. The overall average HE was 0.18863±0.21 for exon1 and 0.03155±0.01. Only four loci, which constitute 10 genotypes, from the polymorphic sites showed significant contribution of litter size of the goat populations studied. Heterozygous genotypes (TC and GC at g.950T>C and g.3416G>C, respectively) had performed highest estimates of litter size in three of the loci which contributed for litter size. However, the homozygous genotype observed at locus g.3811C>T showed highest contribution for fecundity trait. 18 to 31% performance differences of litter size were observed due to the influence of the genotypes. In conclusion, the SNP detected in those target regions of the gene confirm the contribution of the KISS1 gene for fecundity trait suggesting importance of the gene for marker assisted selection in goat breeding programs.